E-Commerce Impact on Small Companies - Surya, A; Nugraha, R F (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to determine how much influence e-commerce has on small companies. The type of research method used was descriptive method by examining the results of several studies. The results of this study were that e-commerce was able to increase the number of sales and expand market reach. Based on the results of the literature, it was found that the existence of e-commerce can increase the productivity of small companies.